Vascular changes in age-related macular degeneration - Borrelli, Enrico; Viggiano, Pasquale; Mastropasqua, Rodolfo (Annals of Eye Science; Vol 4 (January 2019): Annals of Eye Science, 2019)
Age-related macular degeneration (AMD) is considered one of the principal causes of vision impairment among older individuals in developed countries. Assuming this, new technologies which may increment insights elucidating the morphological characteristics of this disorder are expected to improve the visual prognosis in AMD. The development of optical coherence tomography angiography (OCTA) has outstandingly extended our knowledge on the AMD pathophysiology.